Digital Word of Mouth, Destination Attractiveness, Brand Image, Accessibility Drive Tourist Intention: Komunikasi Dari Mulut ke Mulut Digital, Daya Tarik Destinasi, Citra Merek, Aksesibilitas Mendorong Minat Kunjungan Wisatawan - Angelica Putri; Ida Bagus Nyoman Udayana; Lusia Tria Hatmanti Hutami (Academia Open, 2026)
Tourist decision-making in competitive coastal destinations is increasingly shaped by digital exposure, experiential perceptions, and logistical convenience. This study investigates how electronic word of mouth (e-WOM), destination attractiveness, brand image, and accessibility influence tourist visiting intention at a major coastal destination in Indonesia. Using a quantitative ex post facto design, data were collected from 100 purposively selected respondents aged 18 years and above who had visited the destination at least twice and completed a validated Likert-scale survey. Multiple linear regression, supported by t-tests, F-tests, and adjusted R² analysis, reveals that e-WOM, destination attractiveness, brand image, and accessibility each exert a significant positive effect on tourist visiting intention. Collectively, these predictors explain approximately 76.6% of the variance in visiting intention, confirming that digital word of mouth, experiential quality, perceived brand reputation, and travel convenience function as integrated behavioral determinants rather than isolated stimuli. This study contributes empirical evidence to tourism behavior literature by demonstrating that destination competitiveness is strongly anchored in digital influence and multimodal experience rather than physical attraction alone. The findings indicate that enhancing the digital communication ecosystem, strengthening experiential attributes, improving brand positioning, and accelerating access infrastructure are strategic priorities for destination managers seeking to stimulate sustained tourist intention and market resilience. The study offers practical implications for tourism policy, destination marketing organizations, and stakeholders in designing targeted interventions that align with post-pandemic travel patterns and data-driven visitor expectations. Highlights• Digital word of mouth significantly strengthens tourist visiting intention.• Combined predictors explain 76.6% of visiting intention variance.• Brand image, attractiveness, and accessibility jointly sustain destination competitiveness. KeywordsElectronic Word Of Mouth; Destination Attractiveness; Brand Image; Accessibility; Tourist Visiting Intention